Implementasi Teknologi Informasi untuk Meningkatkan Strategi Penjualan pada UKM Driply Coffee Berbasis Online - Wahyuni, Linda; Hardianto, Hardianto; Rosnelly, Rika; Syahrian, Achmad; Rahmadi, Diky (Jurnal Pengabdian Pada Masyarakat METHABDI, 2025)
Small and medium enterprises (SMEs) are similar to the category of Small and medium enterprises (SMEs), but are usually used to refer to small and medium enterprises only, without including micro businesses. Community service carried out at UKM Driply Coffee, which provides types of drinks in the form of coffee and several other types of drinks besides, also providing food that can accompany customers when they come and sit down to relax either alone, with friends, colleagues, or with family. The research conducted looked at the process of its marketing system, which uses social media such as Facebook, Instagram, and also WhatsApp. The system is indeed seen by many customers, only the process for ordering and selecting menus and the payment process cannot all be seen in the display due to the limitations of the image display, from the presentation of these conditions this research was conducted for approximately 3 months, and will be designed and implemented an online-based application that uses a web program and a MySQL database. Customers can access remotely and can also make payments online, and delivery of drinks or food will be carried out according to the intended location. The convenience felt is not only for customers, but partners will also get convenience and be able to compete in the world of small and medium enterprises (UKM).